2017
DOI: 10.3390/antib6030012
|View full text |Cite
|
Sign up to set email alerts
|

Functional, Biophysical, and Structural Characterization of Human IgG1 and IgG4 Fc Variants with Ablated Immune Functionality

Abstract: Engineering of fragment crystallizable (Fc) domains of therapeutic immunoglobulin (IgG) antibodies to eliminate their immune effector functions while retaining other Fc characteristics has numerous applications, including blocking antigens on Fc gamma (Fcγ) receptor-expressing immune cells. We previously reported on a human IgG2 variant termed IgG2σ with barely detectable activity in antibody-dependent cellular cytotoxicity, phagocytosis, complement activity, and Fcγ receptor binding assays. Here, we extend th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 79 publications
(131 reference statements)
0
34
0
Order By: Relevance
“…Hybrid IgG2/4 Fc regions with the Fc with residues 117-260 from IgG2 and residues 261-447 from IgG4 can result in having less FcγR activity. Crystal structures and simulations of IgG1σ, IgG4σ1, and IgG4σ2 Fc variants reveal altered conformational preferences within the lower hinge and BC and FG loops relative to wild-type IgG, providing a structural rationalization for diminished Fc receptor engagement [406].…”
Section: Mutations That Modulate Effector Functionmentioning
confidence: 95%
See 1 more Smart Citation
“…Hybrid IgG2/4 Fc regions with the Fc with residues 117-260 from IgG2 and residues 261-447 from IgG4 can result in having less FcγR activity. Crystal structures and simulations of IgG1σ, IgG4σ1, and IgG4σ2 Fc variants reveal altered conformational preferences within the lower hinge and BC and FG loops relative to wild-type IgG, providing a structural rationalization for diminished Fc receptor engagement [406].…”
Section: Mutations That Modulate Effector Functionmentioning
confidence: 95%
“…In each of these cases, it is best not to stimulate unwanted cell and tissue damage or risk undesired effector cell activation, immune cell depletion, or FcγR cross-linking that might induce cytokine release through engagement of Fc-mediated effector functions [422]. The complexity of FcγR functional properties is increased by the varying densities of activating and inhibitory receptors on the different effector cell populations [406]. Likewise, since the threshold of activation can be variable with different patients, it would be prudent for safety considerations to develop antibodies with a more silent Fc region.…”
Section: Mutations That Modulate Effector Functionmentioning
confidence: 99%
“…[11][12][13] However, incorporation of novel mutations has notable drawbacks including the possibility of decreased stability and increased immunogenicity. 14,15 The glycan profile of IgG mAbs has also been linked to their immune functions, with low fucose IgG glycoforms having improved binding to FcγRIIIa and more potent ADCC. 16 A less established strategy for modulation of effector mechanisms is the duplication of the entire Fc C H 2-C H 3 domains.…”
mentioning
confidence: 99%
“…In line with literature, all molecules comprising an IgG2 σ1 Fc interacted the least with all FcγRs. 39 It has been demonstrated that the limited interaction of IgG2 σ1 with FcγRs in vitro translated to low or no activity in several in vitro functional assays, such as antibody-dependent cell-mediated cytotoxicity (ADCC), complement-mediated cytotoxicity (CDC), and antibody-dependent cellular phagocytosis. 39 This observation confirmed that T cell activity would not likely be mediated via Fc because applied Fc mutations minimized binding to FcγR at the functional concentration ranges of BsAb used in killing experiments although subsets of T cells can express FcγRs.…”
Section: Discussionmentioning
confidence: 99%
“…39 It has been demonstrated that the limited interaction of IgG2 σ1 with FcγRs in vitro translated to low or no activity in several in vitro functional assays, such as antibody-dependent cell-mediated cytotoxicity (ADCC), complement-mediated cytotoxicity (CDC), and antibody-dependent cellular phagocytosis. 39 This observation confirmed that T cell activity would not likely be mediated via Fc because applied Fc mutations minimized binding to FcγR at the functional concentration ranges of BsAb used in killing experiments although subsets of T cells can express FcγRs. 40 Single-arm affinities to CD19 and CD3 were recorded within a range of < 3X for all molecules, revealing that neither the IgG subclass nor molecular format (antibody vs. BsAb) significantly affected affinity in vitro.…”
Section: Discussionmentioning
confidence: 99%